The Use of Generative AI as an Assistant for Public Health Researchers - Kaewsombat, Kuttiya; Khunpiluek, Issara; Kawosombat, Mittaphap (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2025)
Generative AI has emerged as a technology that plays a significant role in various fields, including public health research. This article aims to explain the meaning of Generative AI and analyze its role as an assistant to public health researchers, focusing on four key issues: 1) how to use AI in the research writing process, 2) the credibility of academic work generated by AI, 3) the risk of plagiarism, and 4) perspectives on the use of Generative AI in research in 2025 and beyond. The author has extensively reviewed relevant literature to obtain comprehensive and up-to-date information. The results indicate that although Generative AI has high potential to be a research assistant, there are still ethical, credibility, and appropriate usage concerns that need to be taken into account. Therefore, researchers should understand the limitations of AI while leveraging its benefits to ensure that public health research develops in a direction that truly aligns with human and societal needs.